Study of effect of zoledronic acid on back pain in patients with osteoporosis - Parikh, Kushal N.; Patel, Dhruv M.; Adodariya, Yogenkumar A. (International Journal of Research in Orthopaedics, 2025)
Background: The objective of the study was to assess functional result in back pain treated with a Zoledronic acid. Methods: A prospective observational study was conducted over period of 18 months. SMIMER-Surat Municipal Institute of Medical Education and Research, Surat, Gujarat, India. Thirty-eight patients with various stages of back pain treated with zoledronic acid fulfilling selection criteria admitted in department of orthopaedics in tertiary health care hospital in Surat. Follow up was done after 2nd and 6th month and recording of pain relief in term of VAS and MODQ score. Results: We expected that Patients after receiving Zoledronic acid shows an appreciable and statistically significant improvement in back pain & related complains as well as improvement in monthly follow-up period compared to previous status based on VAS score & MODQ. Conclusions: Our findings have shown that there is a statistically significant improvement in complain of back pain over period of 6 months as compared to previous status of patient.